Políticas públicas de inclusão: o surdo no sistema de educação básica regular do Estado de São Paulo - Lourenço, Katia Regina Conrad (2013)
This dissertation, shod in public policies of inclusive education, aims to investigate how far applicability of the same has been happening in a municipality in the State of SÃ£o Paulo from the point of view of the Deaf student. The history of inclusive education presents major changes and transformations in the course of the history of this nation. Since the 19th century this proposal, together with its laws, guidelines, etc. are being organized, adapted and applied to Brazilian education. However, some events in the year of 2011 brought suspicions in relation to a possible subject oppressed in this process. At the beginning of the year above the Ministry of Education MEC demanded the closing of bilingual schools for Deaf People claiming social segregation of same. From there, struggles, protests and political events have happened and intensified by several regions of Brazil during the course of this year; acirrando the confrontation between an educational policy linguistic - Bilingualism: Libras is the mother tongue and Portuguese Language, second language - and an inclusive educational policy, by which the Deaf - not accepted as subjects of a cultural individuality - should study in regular schools and classes. This whole 2-2 emanates from an epistemological concern and the need for research. Therefore, to achieve the objective of this research, it has also been proposed: A) Present the historical trajectory, the key moments in favor of the education of the Deaf; b) Trace the legal and political advances of inclusion with focus on students with deafness; c) Check the inclusive education in practice with Deaf students; (d) Check what other surveys/ literatures have to contribute with this theme. In This way, were used as research instruments, the bibliographic research and observation in the field. It is believed that this research contributes to the debate and reflection on the real social inclusion of Deaf People